Structural Health Monitoring Using Wireless Technologies: An Ambient Vibration Test on the Adolphe Bridge, Luxembourg City - Adrien Oth; Matteo Picozzi (Advances in Civil Engineering)
Major threats to bridges primarily consist of the aging of the structural elements, earthquake-induced shaking and standing waves generated by windstorms. The necessity of information on the state of health of structures in real-time, allowing for timely warnings in the case of damaging events, requires structural health monitoring (SHM) systems that allow the risks of these threats to be mitigated. Here we present the results of a short-duration experiment carried out with low-cost wireless instruments for monitoring the vibration characteristics and dynamic properties of a strategic civil infrastructure, the Adolphe Bridge in Luxembourg City. The Adolphe Bridge is a masonry arch construction dating from 1903 and will undergo major renovation works in the upcoming years. Our experiment shows that a network of these wireless sensing units is well suited to monitor the vibration characteristics of such a historical arch bridge and hence represents a low-cost and efficient solution for SHM.